The world's northern most harbour seal population - How many are there? - Merkel, Benjamin (Universitetet i Tromsø, 2012)
This study presents the first abundance estimate for the world's northernmost harbour seal (Phoca vitulina) population, which resides in Svalbard, Norway, based on three digital stereoscopic photographic surveys conducted in 2009 and 2010. The counts from these high resolution 3D images were combined with a novel method for estimating correction factors for animals that were in the water at the time of the surveys, in which extensive behavioural data from radio-tagged harbour seals were used together with a modelled stationary age structure to estimate the proportion of seals of various age and sex classes hauled out at the times of the surveys. To detect possible seasonal shifts in age distribution between surveys, lengths of hauled out seals were measured from the stereoscopic images. No such length differences were detected; but, this may be due to a high degree of sexual dimorphism exhibited in this population. Applying the modelled correction factors, a total of 1888 (95 % CI: 1660-3023), 1742 (1381-3549) and 1812 (1656-4418) harbour seals were estimated for the surveys flown on 01 August 2009, 01 August 2010 and 19 August 2010, respectively.The similarity between the three survey estimates (despite significant differences in the number of animals actually counted on the photos from each survey effort) suggests that the variation in numbers of hauled out seals is reasonably accurately adjusted for by the correction factor model. The low population size, the limited spatial distribution of the population and its reduced genetic diversity make it vulnerable to stochastic mortality events. However, barring disease events, climate change—a major threat to many arctic marine mammals—is likely to have a positive impact on this population as more suitable habitat becomes available and competition from endemic arctic pinnipeds is reduced.